Sclerostin and DKK1 Inhibition Preserves and Augments Alveolar Bone Volume and Architecture in Rats with Alveolar Bone Loss. (August 2018) - Liu, M.; Kurimoto, P.; Zhang, J.; Niu, Q.T.; Stolina, M.; Dechow, P.C.; Feng, J.Q.; Hesterman, J.; Silva, M.D.; Ominsky, M.S.; Richards, W.G.; Ke, H.; et al.
Alveolar bone is a mechanosensitive tissue that provides structural support for teeth. Alveolar bone loss is common with aging, menopause, tooth loss, and periodontitis and can lead to additional tooth loss, reduced denture fixation, and challenges in placing dental implants. The current studies suggest that sclerostin and DKK1, which are established osteocyte-derived inhibitors of bone formation, contribute to alveolar bone loss associated with estrogen ablation and edentulism in rats. Estrogen-deficient ovariectomized rats showed significant mandibular bone loss that was reversed by systemic administration of sclerostin antibody (SAB) alone and in combination with DKK1 antibody (DAB). Osteocytes in the dentate and edentulous rat maxilla expressed Sost (sclerostin) and Dkk1 (DKK1) mRNA, and molar extraction appeared to acutely increase DKK1 expression. In a chronic rat maxillary molar extraction model, systemic SAB administration augmented the volume and height of atrophic alveolar ridges, effects that were enhanced by coadministering DAB. SAB and SAB+DAB also fully reversed bone loss that developed in the opposing mandible as a result of hypo-occlusion. In both treatment studies, alveolar bone augmentation with SAB or SAB+DAB was accompanied by increased bone mass in the postcranial skeleton. Jaw bone biomechanics showed that intact sclerostin-deficient mice exhibited stronger and denser mandibles as compared with wild-type controls. These studies show that sclerostin inhibition, with and without DKK1 coinhibition, augmented alveolar bone volume and architecture in rats with alveolar bone loss. These noninvasive approaches may have utility for the conservative augmentation of alveolar bone.